The The Effect of Service Quality and Service Experience on Word Of Mouth (WOM) with Perceived Value As Mediation - Hega Naval Rimba; Noermijati Noermijati; Fatchur Rohman (Journal of Business and Management Review, 2022)
The service industry is one industry that is growing with the times, especially wedding organizer services which are currently overgrowing. Therefore, in February 2021, HASTANA (Association of wedding planning companies) was formed to unite and bring together worldwide wedding organizer companies. Indonesia. This study investigates the factors influencing word of mouth on consumers who use wedding organizers. This study uses word of mouth as the dependent variable that affects service quality, service experience, and perceived value as mediating variables. This research is categorized as explanatory research. Respondents in this study were consumers who had used the services of a wedding organizer, and the determination of the number of samples in this study used a purposive sampling technique with a total sample of 200 respondents. The data collection method used questionnaires, and the data were analyzed using SEM-PLS. The findings of this study indicate that service quality, service experience, and perceived value significantly affect word of mouth. Perceived value also plays a role in mediating the relationship between service quality, service experience, and word of mouth